2022
DOI: 10.1099/mgen.0.000762
|View full text |Cite
|
Sign up to set email alerts
|

The promiscuous and highly mobile resistome of Acinetobacter baumannii

Abstract: Antimicrobial resistance (AR) is a major global threat to public health. Understanding the population dynamics of AR is critical to restrain and control this issue. However, no study has provided a global picture of the whole resistome of Acinetobacter baumannii , a very important nosocomial pathogen. Here we analyse 1450+ genomes (covering >40 countries and >4 decades) to infer the global population dynamics of the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…The A. baumannii isolates in this study belonged to diverse sequence types (STs) representing four International clones, ICs (IC1/CC1, IC2/CC2, IC7/CC25, and IC8/CC10), one clonal complex, i.e., CC862, and one singleton ( Table 2 ). Although genes that confer resistance to different antimicrobials were identified across all clonal lineages, the majority of the genes that encode for aminoglycoside modifying enzymes, RMTases, macrolide resistance, sulfonamide resistance, chloramphenicol, and rifampicin resistance were confined to isolates belonging to IC2 ( Rodrigues et al, 2021 ; Hernández-González et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…The A. baumannii isolates in this study belonged to diverse sequence types (STs) representing four International clones, ICs (IC1/CC1, IC2/CC2, IC7/CC25, and IC8/CC10), one clonal complex, i.e., CC862, and one singleton ( Table 2 ). Although genes that confer resistance to different antimicrobials were identified across all clonal lineages, the majority of the genes that encode for aminoglycoside modifying enzymes, RMTases, macrolide resistance, sulfonamide resistance, chloramphenicol, and rifampicin resistance were confined to isolates belonging to IC2 ( Rodrigues et al, 2021 ; Hernández-González et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“… 3 Importantly, a 2022 study has shown that the resistome of A baumannii is highly mobile, showing many cases of horizontal gene transfer with other important human pathogens such as Klebsiella pneumoniae and Pseudomonas aeruginosa . 9 In connection with the previous point, even if the animal clones of A baumannii do not pose a public health risk per se , the antibiotic genes within them can be horizontally transferred to isolates from other human relevant bacterial species, which could be risky.…”
mentioning
confidence: 98%
“…One isolate from a pig fecal sample (PF33) was discarded as it showed a high percentage of contamination (>60%). For the phylogenetic analysis, we also included 148 human-related A. baumannii genomes previously genotyped in Hernández-González et al ( 15 ). These genomes were chosen as they are part of the eight main international clones (ICs).…”
Section: Observationmentioning
confidence: 99%